OP0220 Pathogenic Role of IL-10 Producing Helper T Cells in Systemic Lupus Erythematosus. (10th June 2014) - Facciotti, F.; Penatti, A.E.; Zeni, S.; Abrignani, S.; Meroni, P.; Geginat, J.
Abstract : Background: IL-10 is a potent anti-inflammatory cytokine that contributes to the suppressive functions of regulatory T-cells, but it is also a well-known B cell growth and differentiation factor produced by CD4+ helper T-cells. Consequently, IL-10 is pathogenic in systemic lupus erythematosus (SLE) where it promotes autoantibody production and nephritis. We have previously shown that human CCR6+ memory T cells produce IL-10 in secondary lymphoid organs, and more recently we found that they promote B cell antibody production via IL-10, but are distinct from follicular helper (TFH ) and Th17 cells. Objectives: To monitor the frequency and function of IL-10-producing B helper T cells in SLE patients and to evaluate their association with disease activity. Methods: Blood samples from 40 clinically well-characterized SLE patients and 25 healthy donors (HD) were included. Composition of different T cell subsets in peripheral blood according to surface markers expression and intracellular cytokine production were assessed by flow cytometry. The frequencies of T cell subsets were correlated with disease activity (measured by the SELENA-SLEDAI index). To assess B helper functions, T cell subsets and B cells from SLE patients and HD were co-cultured ex vivo and IgG production was measured in supernatants by ELISA. Results: IL10-producing CCR6+ memory T cells, but not TFH cells were significantly expanded in the peripheral blood of SLE patients as compared to HD. Importantly, the frequency of CCR6+ memory T cells and serum levels of IL-10, but not of IL-17, correlated with disease activity. Ex vivo sorted CCR6+ helper T cells from blood of SLE patients produced high levels of IL-10 upon co-culture with B cells and promoted IgG production. Strikingly, CD25+ Tregs suppressed B cell help provided by CCR6+ T cells in HD, but not in SLE patients. Conclusions: Our results demonstrated that accumulation of IL-10-producing CCR6+CD4+ memory T cells correlates with SLE disease activity, supporting a pathogenic role of these helper T cells.This hypothesis is corroborated by functional experiments, which demonstrate a Treg-resistant B helper capacity of IL-10-producing CCR6+ T cells in SLE patients. Therefore, CCR6+IL10-producing helper T cells represent a potential therapeutic target and/or diagnostic/prognostic marker of disease activity in SLE patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5485